Fucosyltransferase 4 upregulates P-gp expression for chemoresistance via NF-κB signaling pathway - Cai, Zixuan; Isaji, Tomoya; Liang, Caixia; Fukuda, Tomohiko; Zhang, Dongmei; Gu, Jianguo (Biochimica et biophysica acta. General subjects, 2025)
Multidrug resistance (MDR) poses a significant obstacle to developing chemotherapeutic treatments. In previous studies using a traditional model of adriamycin resistance (ADR) with K562 cells, we demonstrated that N-acetylglucosaminyltransferase III (GnT-III) expression negatively regulates chemoresistance. Additionally, we observed that fucosylation levels were increased in the ADR cells. Fucosylation levels were determined using lectin blot, western blot, and flow cytometry. Gene expression levels were analyzed via qPCR. We generated a FUT4 knockout (KO) ADR cell line using CRISPR/Cas9 technology. Cytotoxicity and drug efflux assays were conducted to evaluate chemotherapy tolerance. The expression levels of FUT4 and its products, the LeX antigens, were significantly upregulated in the ADR cells compared to the parental K562 cells. The FUT4 KO reduced the elevated levels of P-glycoprotein (P-gp) found in ADR cells and exhibited increased sensitivity to chemotherapeutic drugs. Furthermore, restoring FUT4 expression in the KO cells effectively reversed P-gp expression, drug efflux, and chemoresistance. Given the critical role of the NF-κB pathway in P-gp expression, we investigated NF-κB signaling and found that the phosphorylation levels of p65 were significantly increased in the ADR cells but were downregulated in the FUT4 KO cells. Furthermore, the restoration of FUT4 rescued the phosphorylation levels of p65. FUT4 specifically upregulates P-gp expression related to chemoresistance through the NF-κB signaling pathway. This study highlights the importance of FUT4 in chemoresistance and suggests it may serve as a promising target for combating MDR. •The expression levels of FUT4 and its product, the LeX epitope, were significantly elevated in adriamycin resistance of K562 cells.•FUT4 deficiency suppressed P-glycoprotein (P-gp) expression, chemoresistance, and NF-κB signaling, whereas overexpression promoted these characteristics.•FUT4 might be a promising target for combating multidrug resistance.